Editor's Highlight: Ah Receptor Activation Potentiates Neutrophil Chemoattractant (C-X-C Motif) Ligand 5 Expression in Keratinocytes and Skin. (14th August 2017) - Smith, Kayla J.; Boyer, Jacob A.; Muku, Gulsum E.; Murray, Iain A.; Gowda, Krishne; Desai, Dhimant; Amin, Shantu G.; Glick, Adam B.; Perdew, Gary H.
Abstract: Chemokines are components of the skin microenvironment, which enable immune cell chemotaxis. Traditionally, transcription factors involved in inflammatory signaling (eg, NFκB) are important mediators of chemokine expression. To what extent xenobiotics and their associated receptors control chemokine expression is poorly understood. The aryl hydrocarbon receptor (AHR) is a ligand-activated transcription factor known to mediate physiological responses in the skin through the regulation of genes involved in xenobiotic metabolism, epidermal differentiation, and immunity. Here, we demonstrate that AHR activation within primary mouse keratinocytes regulates the expression of a neutrophil directing chemokine (C-X-C motif) ligand 5 ( Cxcl5 ). AHR-mediated regulation of Cxcl5 is because of direct transcriptional activity upon treatment with AHR agonists such as 2, 3, 7, 8-tetrachlorodibenzo- p -dioxin (TCDD). Additionally, AHR mediates enhanced induction of Cxcl5 upon exposure to an agonist and the inflammatory cytokine interleukin 1 beta. This synergy is confined primarily to keratinocytes, as dermal fibroblasts did not achieve the same level of combinatorial induction. AHR-specific antagonists were able to reduce basal and induced levels of Cxcl5, demonstrating the potential for pharmacological intervention. Exposure of C57BL/6 J mice to ultraviolet (UV) light followed by topical treatment with the AHR agonist formylindolo(3, 2-b)carbazole (FICZ) significantly induced Cxcl5 expression in skin compared with UV alone, and this response was absent in Ahr −/− mice. These results establish AHR as an important mediator of Cxcl5, with implications for the treatment of inflammatory skin diseases.